Hr Analytics: Data-Driven Decision Making Dalam Sdm Dinas Perhubungan Sumatera Barat - Yuliana Fransiska; Hairul Patwa; Muhammad Ridho; Wulandari .; Rendi Zaputra; Vivi Nila Sari (CV. ITTC INDONESIA, 2026)
HR Analytics is a data-driven approach used to support decision making in human resource management. This study aims to analyze the implementation of HR Analytics in data-driven decision making within the human resources management of the West Sumatra Provincial Transportation Agency. The research employs a descriptive approach using secondary data, including personnel records, attendance data, and performance reports. The results indicate that HR Analytics provides accurate information to support decision making related to workforce planning, performance evaluation, and human resource development. The implementation of HR Analytics contributes to improving evidence-based human resource management in the public sector.